Analysis of Economic Viability of Renewable Energy Projects in the Brazilian and Piauí Scenario, with a Global Perspective and the Role of China - da Rocha, Tarcísio (Latin American Journal of Energy Research, 2025)
This work analyzes the economic viability of renewable energy projects in Brazil, focusing on the specificities of the State of Piauí, considering the regulatory framework of the National Electric Energy Agency (ANEEL) and the impact of energy auctions. Additionally, the global scenario is discussed, with particular attention to China's role as a catalyst for innovation and cost reduction, and the influence of United Nations (UN) initiatives in promoting the energy transition. In this analysis, both the factors driving the attractiveness of these investments and the structural and operational challenges, such as the intermittency inherent to renewable sources, transmission infrastructure, and bureaucratic processes, are addressed. The main financial indicators and government incentives that shape the attractiveness of these investments are also covered, highlighting the role of public policies in fostering the energy transition.
Keywords: Renewable energy; economic viability; Piauí; China; energy transition